2019
DOI: 10.3390/app9204343
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Seismically-Induced Crest Settlement of Earth Core Rockfill Dams

Abstract: The settlement at the dam crest induced by earthquake loading is an important design parameter widely used to evaluate the seismic performance of dams. Two-dimensional nonlinear dynamic analyses were performed to calculate the dam crest settlement of earth core rockfill dams (ECRDs). The numerical model was first validated against centrifuge test measurements. Comparisons showed that the numerical model provided reasonable estimates of the measured response. A series of dynamic numerical analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In addition, comparing the values of D C in Table 3 with those obtained using Equation ( 8) when H d is assumed equal to 48 m (as for the San Pietro and the Marana Capacciotti dam) or to 57 m (as for the Camastra dam) an underestimation of about 24% and an overestimation of about 30% of the crest settlement are, respectively, obtained. This observation permits tentatively concluding that for a generic earth dam, using only the height H d as input datum, Equation (8), calibrated on (the few) available field data, along with Equation ( 9), leads to a fair assessment of the earthquake induced crest settlement.…”
Section: Dammentioning
confidence: 77%
See 4 more Smart Citations
“…In addition, comparing the values of D C in Table 3 with those obtained using Equation ( 8) when H d is assumed equal to 48 m (as for the San Pietro and the Marana Capacciotti dam) or to 57 m (as for the Camastra dam) an underestimation of about 24% and an overestimation of about 30% of the crest settlement are, respectively, obtained. This observation permits tentatively concluding that for a generic earth dam, using only the height H d as input datum, Equation (8), calibrated on (the few) available field data, along with Equation ( 9), leads to a fair assessment of the earthquake induced crest settlement.…”
Section: Dammentioning
confidence: 77%
“…As an example, using either field data, relative to postseismic surveys, or numerical predictions, obtained through advanced finite difference or finite element analyses, relative to different types of earth dams, several studies showed the relationship between the permanent crest settlement and the peak ground acceleration or velocity (e.g., Lanzo et al, 6 Lanzo, 7 Park et al, 8 Ghaemi and Konrad, 4 Armstrong et al, 9 Regina et al 10 ), the Arias Intensity (e.g., Yule et al, 11 Sica and Pagano 5 , Brigante and Sica, 12 Pagano and Sica, 13 Lanzo et al, 6 Lanzo, 7 Park et al, 8 Armstrong et al, 9 Cascone et al, 14 Regina et al 10 ), the cumulative absolute velocity (i.e. the integral of the acceleration time-history, e.g., Lanzo et al, 6 Armstrong et al, 9 Regina et al 10 ), the bracketed (e.g., Yule et al, 11 for a threshold acceleration equal to 0.05 g) or the strong motion (Lanzo et al, 6 Armstrong et al, 9 Cascone et al, 14 Regina et al 10 ) duration, the specific energy density (i.e., the integral of the squared velocity time-history; e.g., Lanzo et al 6 ), the destructiveness potential factor (e.g., Cascone et al 14 ), the mean or the predominant period (e.g., Lanzo et al, 6 Ghaemi and Konrad 4 ) and, finally, the pseudo spectral acceleration computed for different vibration periods (e.g., Armstrong et al, 9 Regina et al 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations